ANALISA PERENCANAAN KONSTRUKSI STRUT PROPELLER DENGAN PROFIL NACA - Riska Amaliyah; Raden Dimas Endro Witjonarko; Nurvita Arumsari (Politeknik Perkapalan Negeri Surabaya, 2020)
important constructions is the construction of propeller strut. The propeller strut is a support consistingof an arm and a bearing that is attached between the propeller shaft and the hull on the stern of the ship. In thisstudy, a modification was made to the propeller strut construction with the cross-sectional shape of the terrain insuch a way that it gave the shape of the cross-sectional profile of the National Advisory Committee of Aeronautics(NACA) and formed a solid cylinder. This alternative strut design is modeled and simulated using the CFD tool inthe ANSYS CFX software so that the average velocity, streamline flow, and pressure on the strut are known. Andexpressions with optimization with the particle swarm optimization method. The results of this study found that theNACA profile 16-021 is the best and efficient profile among 2 other profiles.